Preparation and Performance of Bamboo Fiber/Polypropylene Intertwined Braided Composite - Haiyu Xu, Wei Zhang, Yinwei Wu, Wenbin Yao (Forest Chemicals Review, 1970)
Bamboo fibers (BF) and polypropylene (PP) fibers are processed into BF/PP intertwined ropes by twisting separate yarns. After plain weaving, low-PP (less than 30%) composite materials are prepared by the thermal drying-hot press process. The effects of the PP fiber content on the mechanical performance, thermal performance, and water absorption ability of the composite materials are studied. As the content of the PP fiber increases, the tensile strength of the composite material decreases and its flexural strength increases. Thermal analysis and water absorption experiments show that with increasing polypropylene content, the thermal stability of the composite material increases, whereas the moisture absorption ability decreases. The SEM analysis of the composite obtained show that interface combination of the two phases and mechanical properties would be improved. The trial show that the BF/PP composite with the mass ratio of 83:17 had the better comprehensive properties. Compared with the non-braided BF/PP composite, the tensile and flexural strengths are both improved. Our study could offer a making method and insights for the BF/PP weaving composite, which may be of help on the design of green materials in interior building and decoration.